Advances in CAR-T Cell Therapy for Treating Acute Myeloid Leukemia: Challenges and Future Perspectives - MG, Vishnu; Rahul; Jocelin Harriate; Sruthi (Jurnal Kebidanan Manna, 2024)
This review focuses on the revolutionary capacity of CAR-T therapy in the context of acute myeloid leukemia (AML). It is an area beset with challenges despite its progress in the treatment of hematologic malignancies. Specifically, it narrows down to identifying ideal target antigens such as CD33, CD123, and FLT3 which are pertinent to the challenge of antigen heterogeneity in AML as well as minimizing on-target off-tumor toxicity. These problems are attempted to be eliminated through innovative concepts like the use of dual-targeting CARs, armoured CAR-T cells, and CRISPR-mediated genetic editing techniques, each having a superior safety and efficacy profile.Dual-target CARs have the advantages of improved selectivity; armoured CAR-T cells can survive in the AML immunosuppressive microenvironment, and CRISPR-mediated CAR-T cells ensure precision with minimal side effects. The clinical outcomes in the last few years and a string of recent preclinical studies show promising, albeit challenging, therapeutic results. In any case, such observations mark significant progress toward ensuring long-term remission while tolerable toxicity levels. This chapter draws upon recent clinical trials and research findings in order to put into sharp relief CAR-T therapy's emergent role as a new, life-saving approach for the treatment of AML. Its understanding of technological advancement in CAR-T therapy places this chapter as an invaluable reference source for researchers and clinicians interested in optimizing CAR-T therapy in the treatment of AML